Epistemology of PMI Dawah Science Based on Social Welfare (Social Welfare) - Hidayatulloh, Asep; Syukur, Abdul (EDUCATIO : Journal of Education, 2022)
This study delves into the epistemology of Da'wah Science as applied by the Center for the Study of Islamic Community Development (PMI), focusing on the socially welfare-based approach known as "Social Walfer." It reveals how this epistemology supports the social empowerment of Muslim communities and its influence on PMI's role in enhancing the well-being of these communities. Using qualitative methods involving document analysis, interviews, and literature review, this research investigates PMI's Da'wah Science epistemology centered on social welfare (Social Walfer). The findings highlight that PMI's Da'wah Science fosters respect for religious and cultural diversity, universal values, the incorporation of religious perspectives in addressing social issues, and community empowerment through education and advocacy. It promotes interfaith and intercultural dialogue, reinforcing a solid scientific and philosophical foundation that enables wise interactions with diverse communities, resulting in a harmonious and sustainable society. PMI's Da'wah Science offers inclusivity, intercultural dialogue, tolerance, cooperation, and the formulation of relevant messages for various social and religious groups, holding significant potential in building an inclusive, diverse, and sustainable society.